2020
DOI: 10.1101/2020.10.06.328757
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phylogeographic analysis of shrubby beardtongues reveals range expansions during the Last Glacial Maximum and implicates the Klamath Mountains as a hotspot for hybridization

Abstract: Quaternary glacial cycles often altered species’ geographic distributions, which in turn altered the geographic structure of a species’ genetic diversity. In many cases, glacial expansion forced species in temperate climates to contract their ranges and reside in small pockets of suitable habitat (refugia), where they were likely to interact closely with other species, setting the stage for potential gene exchange. These introgression events, in turn, would have degraded species boundaries, making the inferenc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…All processed sequence reads, scripts, and output files for analyses conducted in this manuscript have been made available on Dryad (Stone & Wolfe, 2021; https://doi.org/10.5061/dryad. n5tb2 rbtf).…”
Section: Data Ava I L a B I L I T Y S Tat E M E N Tmentioning
confidence: 99%
“…All processed sequence reads, scripts, and output files for analyses conducted in this manuscript have been made available on Dryad (Stone & Wolfe, 2021; https://doi.org/10.5061/dryad. n5tb2 rbtf).…”
Section: Data Ava I L a B I L I T Y S Tat E M E N Tmentioning
confidence: 99%
“…For example, average temperatures in the LGM were substantially colder than they are today, and became increasingly hot after the LGM, reaching a temperature peak near the MID (Otto-Bliesner et al, 2006;Renssen et al, 2009;Wanner et al, 2008). The dramatic fluctuations in climate had a significant impact on species distributions, resulting in fragmented habitats among populations or more overlapping in species ranges between relatives (Hewitt, 1999;Stone & Wolfe, 2021). So we expected that the strength of the ecogeographic barrier between related species could be dynamic and change over time as a consequence of climate changes.…”
Section: Ecogeographic Isolation In the Pastmentioning
confidence: 99%
“…Unlike the classical paradigm of temperate species' responses to glaciation, we found that only one species, A. rockii, contracted its ranges to small pockets of suitable habitat, while the other three species experienced an increase in suitable habitat during the LGM relative to the present day. A recent study on Penstemon species in the Pacific Northwest of North America also experienced increased suitable habitat during the GLM, resulting in gene exchange between species (Stone & Wolfe, 2021).…”
Section: Ecogeographic Isolation In the Pastmentioning
confidence: 99%